Uterine Compression Sutures as an Effective Treatment for Postpartum Hemorrhage: Case Series - Nihal Al Riyami; Dini Hui; Elaine Herer; Ori Nevo (Thieme Medical Publishers, Inc., 2011)
We evaluated the role of uterine compression sutures as a conservative treatment for postpartum hemorrhage (PPH) after failed medical treatment. We retrospectively reviewed the charts of all patients who delivered between 2003 and 2009 at a single tertiary care center and who underwent uterine compression sutures for PPH. Twelve women had uterine compression sutures for PPH. The mean age of the patients was 36.3 ± 5.2 years. The mean gestational age at delivery was 37.7 ± 2.0 weeks, and the average estimated blood loss was 2.1 ± 1.1 L. The mean procedure time to perform the uterine compression sutures was 9.3 ± 2.8 minutes. The success rate of compression sutures was 92% with only one failure resulting in a hysterectomy. Uterine compression sutures are an effective method for the treatment of PPH, thus avoiding hysterectomy and preserving potential fertility.